NATIVE TITANIUM IN GRANITOID ROCKS OF THE BEZYMYANNYY PLUTON, EASTERN YAKUTIA - Trunilina V.A.; Royev S.P.; Zayakina N.V.; Makhotko V.F. (My University, 1988)
While studying accessory minerals in an artificial heavy mineral concentrate from the Bezymyannyy pluton, we found for the first time a pure native titanium grain. Besides native titanium, samples contained native tin, lead, copper, iron, zinc, nickel, gold and aluminum, as well as intermetallic tin-antimony and copper-zinc compounds. Impurities in the native iron are sodium, potassium, silicon and aluminum. In other words, the group includes petrogenic elements that were part of the leucogranite melt and ore elements characteristic of the deposits in the same area.